PENGARUH DISIPLIN KERJA, KEPUASAN KERJA DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA HOTEL GRAND ZURI KUTA - Made Dwi Suryadinata; A.A. Dwi Widnyani; Tiksnayana Vipraprastha (VALUES, 2022)
Human resources (HR) is a major factor in achieving company goals. One of the important roles of human resources in a company is to synergize other company resources such as humans, machines, money, methods, and materials. So the company will achieve its goals. Employee performance is the result of work achieved by a person or group of people in an organization or company, according to their respective authorities and responsibilities in the context of achieving company goals. The factors that influence employee performance in this study are work discipline, job satisfaction, incentives. This study aims to determine the effect of work discipline, job satisfaction, incentives on employee performance at the Grand Zuri Kuta Hotel. The population in this study were all employees of the Grand Zuri Kuta Hotel with a total of 58 employees. Samples were taken using a saturated or census sample, so that will be used as a sample in this study is the entire population taken, namely a total of 58 employees. Data collection methods used in this study are observation, interviews, documentation, questionnaire methods. This study used multiple regression analysis techniques with the SPSS version 24 for windows analysis tool. The results showed that partially work discipline has a positive and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance, incentives have a positive and significant effect on employee performance. Variables of work discipline, job satisfaction, incentives jointly affect employee performance.